The Role of Causal and Contextual Conditions in Identifying Entrepreneurial Opportunities in Network Marketing: An Analytical Perspective from Experts - Alizadeh Seyghalan, Hamzeh; Taghvaee Yazdi, Maryam; Nasimi, Mohammad Ali (Digital Transformation and Administration Innovation, 2026)
Network marketing, as one of the modern business models, has provided a significant capacity for creating entrepreneurial opportunities. However, the emergence of such opportunities depends on a set of causal and contextual conditions that have not yet been systematically analyzed. The purpose of this study is to identify and explain the causal and contextual conditions that influence the process of entrepreneurial opportunity formation within the context of network marketing in Iran. This study was conducted using a qualitative research design based on the grounded theory approach. Data were collected through semi-structured interviews with 12 experts in the fields of entrepreneurship, marketing, and network management, and analyzed through open, axial, and selective coding. The findings indicated that causal conditions such as economic motivation, job dissatisfaction, and the pursuit of occupational independence, along with contextual conditions such as legal structures, social culture, professional education, and information technology infrastructure, play a decisive role in identifying and exploiting entrepreneurial opportunities in this field. Accordingly, the proposed conceptual model of the study illustrates the dynamic interaction among these factors as a prerequisite for the emergence of sustainable opportunities. The results of this study can assist policymakers, network marketing practitioners, and entrepreneurs in designing more effective strategies for the development of network marketing–based businesses by gaining a more accurate understanding of environmental and causal conditions.